STRATEGI PEMASARAN SEKOLAH DALAM MENINGKATKAN MINAT PESERTA DIDIK BARU DI SMP YAYASANPENDIDIKAN KARYA SIMANTIN KABUPATEN SIMALUNGUN - May Sari Purba Siboro (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2020)
School marketing strategy is a process of offering goods and services that aim to attract students to attend these private educational institutions. Meanwhile, the interest of new students is an interest of students / parents towards an educational institution without any coercion to develop the potential that exists within them according to their stage of development. The purpose of this research is to find out the School Marketing Strategy in Increasing the Interest of New Students at SMP Yayasan Pendidikan Karya Simantin. Simalungun Regency. The research model was carried out by distributing questionnaires to class VII students as a sample and 51 students as respondents who then processed the data using SPSS version 23 software. new learners as the dependent variable. The sample in this study amounted to 51 respondents. The results of data processing showed that the coefficient of Y = 9.484 + 0.743 X, indicating a constant value (a = 9.484) and (b = 0.743). By comparing between t count and t table, namely t count (6.976) is greater than t table (2.009), which means that school marketing strategies have a significant effect on the interest of new students. The R squer table shows that the adjusted coefficient of determination (R squer) is 0.764 or 76,4% meaning that the interest of new students is influenced by the school's marketing strategy of 76,4% while 23% is influenced by other external variables. this research such as school quality, facilities and others.